Membantu pembuatan plang jalan arah kp. Cikondang desa cikahuripan kecamatan cisolok - Sugih Chandra Kayat (STISIP Widyapuri Mandiri Sukabumi, 2023)
Kp. Cikondang Cikahuripan Village is located in the highlands far remote right under the foot of the mountains, so when we want to know the location of Kp. Cikondang is very difficult to know for people from outside Cibangban Hamlet, especially outsiders who are not people from Cikahuripan Village itself. To be able to quickly find out the location, directions are needed. Therefore, we, the KKM students of Stisip Widyapuri Mandiri Sukabumi, took the initiative to help in making Cikondang Village Road Signs. It is hoped that people outside the hamlet or outside of Cikahuripan Village can easily find the location of Kp. Cikondang. In addition, the spread of information about the existence of Kp. Cikondang which is rarely known by the outside community can quickly spread out of the village because of the many passers-by who see the direction of Kp.Cikondang. KKM students also do not make their own road signs or use existing materials, but we deliberately order road signs from people who are familiar and professional so that the road signs can last a long time.